Exotic Othering of Indigeneity in Khan’s In the Company of Strangers - Afzal, Ayesha; Abbas, Amina (Pakistan Languages and Humanities Review, 2025)
The purpose of this research is to analyze othering of Pakistani people and cultural markers, in addition to, oriental narrative strategies used in Khan’s In the Company of Strangers. The theoretical framework is based on Lau’s Re-Orientalism: The Perpetration and Development of Orientalism by Orientals (2009) and Huggan’s The Postcolonial Exotic (1994) to investigate renewal of oriental discourse with the materialization of new trends including the authorial repositioning and experiential authority of native writers. The textual interpretation is based on McKee’s Textual Analysis: A beginner’s guide (2003). The results of this research reveal that representation of Pakistani Muslims is replete with oriental othering through gender stereotypes to depict men as violent and women as oppressed yet seductive creatures. Moreover, it includes exotic portrayal of Pakistani culture, food and urban spaces as a paradox of sensuousness and mayhem. A re-oriental analysis of Pakistani poetry in English is recommended for further research in this area.